2020
DOI: 10.12688/f1000research.18062.5
|View full text |Cite
|
Sign up to set email alerts
|

Toward a paradigm shift from deficit-based to proactive speech and language treatment: Randomized pilot trial of the Babble Boot Camp in infants with classic galactosemia

Abstract: Background: Speech and language therapy is typically initiated reactively after a child shows delays. Infants with classic galactosemia (CG), a metabolic disease with a known high risk for both speech and language disorders, hold the keys towards evaluating whether preventive treatment is effective when the risks are known at birth. We present pilot data from a randomized parallel trial of an innovative proactive speech and language intervention program, the Babble Boot Camp (BBC). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 46 publications
(3 reference statements)
0
11
0
Order By: Relevance
“…The other interesting approach is the Babble Boot Camp (BBC), which is focused on a proactive speech and language intervention program [ 146 ]. Current guidelines recommend regular extensive screening for speech and language delay, if children do not meet appropriate levels of speech or language treatment is initiated preferably during the first year of life [ 111 ].…”
Section: Potential Therapiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The other interesting approach is the Babble Boot Camp (BBC), which is focused on a proactive speech and language intervention program [ 146 ]. Current guidelines recommend regular extensive screening for speech and language delay, if children do not meet appropriate levels of speech or language treatment is initiated preferably during the first year of life [ 111 ].…”
Section: Potential Therapiesmentioning
confidence: 99%
“…Current guidelines recommend regular extensive screening for speech and language delay, if children do not meet appropriate levels of speech or language treatment is initiated preferably during the first year of life [ 111 ]. However, since speech and language can be regarded as later-developing skill, deficits and signs of delay will only become apparent after an age greater than 24 and 36 months, respectively [ 111 , 146 ]. This approach focuses on a preventive intervention program starting at 2 to 4 months of age and consisting of active parental involvement guided by an expert speech language pathologist.…”
Section: Potential Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Other researchers propose therapy techniques for infants and young toddlers to include encouraging vocalizations and communication more broadly, expanding phonetic inventory, and the use of various syllable shapes (Davis & Velleman, 2000;Fish, 2016). A Babble Boot Camp conducted between 2-24 months for infants with classic glactosemia revealed an increase in the infants' babbling and meaningful speech when parents engaged in daily reinforcement of their infant's babbling, expanding utterances, and shared with their infant in joint book reading (Peter et al, 2020). Shriberg and colleagues (2011) reported that children with glactosemia have higher prevalence rates of CAS (24%) compared to the general population (0.1-0.2%).…”
Section: Furthermore Recent Clinical Trials Of Interventions Commenced During Infancy For Childrenmentioning
confidence: 99%
“…Early treatment reverses the acute manifestations of galactosemia; however, even with treatment, the disease can still cause most patients to develop life-long health complications of the central nervous system in both sexes 5 and primary ovarian insufficiency in women. 6 The majority of the patients present with some cognitive difficulties which increase with age in cross-sectional studies 1,5 but not in longitudinal studies, 7,8 learning disabilities, 9 speech and language disorders, [10][11][12][13][14][15] including apraxia of speech or verbal dyspraxia, 14,16,17 delay in social development, 18,19 and motor dysfunction. 20 These impairments are observed in many patients with galactosemia irrespective of timing of treatment onset and degree of galactose restriction.…”
Section: Introductionmentioning
confidence: 99%